An Algorithmic Approach in Diagnosis and Management of Proptosis: Demographic Patterns, Frequency and Aetiology of Proptosis - Rafique, Aisha; Syeda Alishba Zehra; Ammarah Ashraf; Ubaid Ullah Yasin; Abid Hassan Naqvi (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the demographic patterns, frequency, and etiological profile of proptosis in patients presenting to a tertiary care eye hospital, and to develop an algorithmic approach for its diagnosis and management.Study Design: Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Aug 2024 to Aug 2025.Methodology: Two hundred participants presenting with proptosis over one year were divided into two age groups: 0-30 years, and 30 years and above. All patients underwent detailed ophthalmological examinations, including a comprehensive proptosis assessment, neuroimaging correlation, and systemic evaluation. Data collected included age, gender, visual acuity, pupil response, diplopia, laterality, symptom duration, clinical features, imaging findings, and final diagnosis. An evidence-based diagnostic and management algorithm was developed and implemented to streamline clinical decision-making.Result: Of 200 patients with proptosis, 170(85%) were males and 30(15%) were females. Fifty (25%) were under 30 years of age, while 150(75%) were aged above 30 years. Aetiology comprised endocrinological causes 40(20%), followed by inflammatory 36(18%), systemic 34(17%), arteriovenous malformation 30(15%), pseudo-proptosis 28(14%), infective 26(13%), and idiopathic 6(3%). Surgical intervention was indicated in 68(34%) of patients, while conservative management was employed in 118(59%). Patients underwent both surgical and conservative treatments comprised 14(7%).Conclusion: Endocrinological, inflammatory, and systemic causes were most frequently identified. The suggested diagnostic and management algorithm demonstrated effectiveness in facilitating efficient clinical decision-making.